Development of Electronic Test Instruments Through Vinesa to Improve Statistical Reasoning Ability on Tendency Central Materials - Hari Setyaedhi; Rusijono Rusijono; Hirnanda Pranada (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to assess the feasibility of developing an e-test instrument for statistics courses on central tendency material so that student learning outcomes can increase. The analysis used in this research is quantitative and descriptive. This research method uses 20 students. Methods of data collection using tests, observations, interviews, and questionnaires The procedures carried out in developing the test instrument are: 1) compiling test specifications; 2) writing test questions; 3) reviewing the item items; 4) conducting test trials; 5) analyzing the item items; 6) revising the test; 7) compiling the test; 8) carrying out the test; and 9) interpreting the test results. The ADDIE model is used in this development research. The results of the feasibility of developing electronic test instruments were stated to be valid with: a) the results of validating the material were very feasible (96%); b) the results of validating learning media were very feasible (94%). If c) the results of validating learning designs were very feasible (94%), d) the results of individual trials were very feasible (81%), and e) the results of small group trials were very feasible (82%), then the development of electronic test instruments is very feasible for use in statistical learning.